Mapping security : the corporate security sourcebook for today's global economy - Patterson, Tom (Addison Wesley Professional, 2004)
Praise for Tom Patterson's Mapping Security "Tom Patterson captures a compelling and practical view of security in a multinational environment. Your CSO needs to read this book!"--Dr. Vint Cerf, senior vice president of Technology Strategy at MCI and founder of Internet Protocol (IP) "The power of the Internet is that it's a global network, seamlessly crossing borders. But it also brings security risks that can cross borders just as easily. Patterson has more than a decade of first-hand experience in defending against such risks and it shows. He uses real-world examples and stories, many from his own career, and offers clear, action-oriented descriptions of the different threats and how to deal with them. This book avoids security jargon and speaks directly to businesspeople around the globe." -Chris Anderson, Editor in Chief, Wired Magazine Whether consumers or global giants, we all need to be spending a greater share of our budgets on security. The threats are greater than ever and increasing daily, and yet there is a challenge as to how to justify the expenditure. Mapping Security offers business-oriented and in-depth thinking on how and why to build security into the fabric of the organization. After reading Tom Patterson's book, you will want to make changes with a sense of urgency.-John R Patrick, president of Attitude LLC and former vice president of Internet Technology at IBM Corporation As companies of all sizes go global in their search for profit and growth, they will need to understand how to use security as a tool for success in different markets, and Mapping Security shows them how.-Dr. Craig Fields, former director of Advanced Research Projects Agency (ARPA) for the U.S. Government The Definitive Guide to Effective Security in Complex Global Markets Companies are global today and have complex security supply chains, out-sourced operations, and customer relationships that span the world. Today, more than ever, companies must protect themselves against unprecedented threats, understand and adhere to a global mosaic of regulations, and leverage security to enable today's business realities. In Mapping Security, global security expert Tom Patterson shows how to meet these challenges by presenting security best practices, rules, and customs for virtually every country where you do business. Writing for executives, business managers, security professionals, and consultants, Patterson offers an exceptionally thorough and authoritativ ...